Broadly neutralizing antibody specificities detected in the genital tract of HIV-1 infected women. (24th April 2016) - Mkhize, Nonhlanhla N.; Durgiah, Raveshni; Ashley, Vicki; Archary, Derseree; Garrett, Nigel J.; Karim, Quarraisha Abdool; Karim, Salim S. Abdool; Moore, Penny L.; Yates, Nicole; Passmore, Jo-Ann S.; Tomaras, Georgia D.; Morris, Lynn
Abstract : Background: Broadly neutralizing antibodies (bNAbs) targeting conserved epitopes on the HIV envelope glycoprotein have been identified in blood from HIV-1 infected women. We investigated whether antibodies in the genital tract from these women share similar epitope specificities and functional profiles as those in blood. Methods: Immunoglobulin (Ig)G and IgA antibodies were isolated from cervicovaginal lavages or Softcups from 13 HIV-infected women in the CAPRISA cohort using Protein G and Peptide M, respectively. Binding antibodies to envelope antigens were quantified by ELISA and binding antibody multiplex assay. Neutralizing antibody titers and epitope targets were measured using the TZM-bl assay with Env-pseudotyped wild-type and mutated viruses. Results: HIV-specific IgG, but not IgA, was detected in genital secretions and the ratio of total IgG to HIV-specific IgG was similar to plasma. HIV-specific IgG reacted with multiple envelope antigens, including V1V2, gp120, gp140 and gp41. Two women had high plasma titers of HIV-specific IgG3 which was also detected in their genital tract samples. IgG from the genital tract had neutralizing activity against both Tier 1 and Tier 2 primary HIV-isolates. Antibodies targeting well known glycan epitopes and the membrane proximal region of gp41 were detected in genital secretions, and matched specificities in plasma. Conclusions: Women with plasma bNAbs have overlapping specificities in their genital secretions, indicating that these predominantly IgG isotype antibodies may transudate from blood to the genital tract. These data provide evidence that induction of systemic HIV-specific bNAbs can lead to antiviral immunity at the portal of entry. Abstract : Supplemental Digital Content is available in the text